2010
DOI: 10.1002/adem.200900259
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Austenite in 17–4 Precipitation‐Hardening Stainless Steel Produced by Selective Laser Melting

Abstract: Selective laser melting (SLM) is a rapid prototyping technique based on melting and solidification of powder layers to build up a 3-D solid body. [1][2][3] It was developed as a prototyping technology, but is attracting ever-increasing interest as a rapid manufacturing technology for the production, for instance, of orthopedic prostheses made of titanium and cobalt alloys [4,5] and die inserts made of low alloys and maraging steels for the plastics industry. [6,7] Because of the large solidification undercooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 18 publications
6
72
0
Order By: Relevance
“…Indeed, as-built samples are approximately composed of 70% mass fraction austenite and 30% martensite on average [21]; a reference microhardness of 265 HV is found, in agreement with similar results on the same alloy [22] and the material data sheet of the supplier.…”
Section: Resultssupporting
confidence: 77%
“…Indeed, as-built samples are approximately composed of 70% mass fraction austenite and 30% martensite on average [21]; a reference microhardness of 265 HV is found, in agreement with similar results on the same alloy [22] and the material data sheet of the supplier.…”
Section: Resultssupporting
confidence: 77%
“…Wrought 17-4PH stainless steel is supplied by the mill as a fully martensitic material, which is then heat treated to form copper precipitates, which increase the strength. In contrast, Facchini et al’s [13] analysis showed that the as-fabricated UNS S17400 stainless steel was 70 percent mass fraction metastable austenite, which transformed to the martensite phase during tensile deformation. The material of our study is similar to that of Facchini et al [13], in that the as-fabricated material is not magnetic, and therefore not martensitic, but after deformation the specimens are strongly ferromagnetic.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Facchini et al’s [13] analysis showed that the as-fabricated UNS S17400 stainless steel was 70 percent mass fraction metastable austenite, which transformed to the martensite phase during tensile deformation. The material of our study is similar to that of Facchini et al [13], in that the as-fabricated material is not magnetic, and therefore not martensitic, but after deformation the specimens are strongly ferromagnetic. The deformation-induced austenite-to-martensite transformation is common in austenitic stainless steels and has been studied extensively [14,15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Facchini et al [49] analyze the microstructure and Kumar and Kruth [50] study the wear behavior of SLMfabricated 17-4 steel parts. Murr et al [51] provide a good review on efforts in processing 17-4 PH steel and other metallic alloys using laser-and electron beam-based AM, with a focus on reporting the microstructure and phase structures.…”
Section: Literature Reviewmentioning
confidence: 99%